ANATOMY OF ENTREPRENEURIAL LEADERSHIP AND ADMINISTRATION - Gwakwa, Dr. Milton; Percy Siyavizva, Kudzai (The journal of contemporary issues in business and government, 2022)
Today’s corporates need entrepreneurial leadership. Intricacies in business, coupled with global transformation, are pushing businesses to prioritize sustainability. And entrepreneurial leadership requires having a pool of individuals who are up to work given lack of resources or uncertainties and environmental turbulence and the recent COVID-19 pandemic bedeviling industry. Ordinarily, the possession of leadership qualities by corporate managers is just not sufficient enough to maintain growth, development and sustainability of enterprises. It is at this point that the philosophy of entrepreneurial leadership emerges. The paper explicitly examines entrepreneurial leadership characteristics and entrepreneurial capabilities of the current leaders in the small and medium enterprise. In order to achieve this, the paper systematically reviews the literature to assess the current status of entrepreneurial leaders’ research, highlights knowledge gaps and offers prospective directions for future research. Today, the need for entrepreneurial leaders in businesses is increasing and cannot be overemphasized. The study findings show that there is a strong relationship between entrepreneurial leadership and organizational performance with characteristics’ such as leaders paranoid, confidence, risk taking, proactive, visionary, decisiveness at the fore of entrepreneurial leaders. The need to produce a crop of leaders with cognitive ambidexterity, creative in scope and with predictive logic on how the future is likely to be cannot be overemphasized for corporate sustainability. The present study makes a theoretical contribution by highlighting the importance of EL in fostering team cohesion in the and ultimately driving it to perform better and engage in more innovative behavioursthat sustains organizations.The study further recommends for a crossbreed research on entrepreneurial leadership versus corporate vision across Sub-Saharan region.